Regenerative endodontic: use of autologous platelet-rich fibrin in vital permanent teeth with pulpal pathology. narrative review of the literature (2014)
Currently one of the controversies principals in the treatment of permanent teeth diagnosed with pulpitis is the decision of whether to perform a vital pulp therapy (VPT) or conventional root canal treatment. Different studies have reported achieving of predictable results by performing VPT. Treatment success depends on a proper understanding of the pulp’s biology, strict treatment protocol and adequate case selection. For this purpose, different materials have been suggested. Recently, platelet rich fibrin has been used a biomaterial that fulfills biological requirements to achieve tissue repair. It is important to develop treatments aiming at preserving the vitality of the pulp, avoiding the conventional root canal treatment as a first choice and aiming at preserving or regenerating the dentin-pulp complex.